The Current European Perspective on the Exequatur of U.S. Punitive Damages: Opening the Gate But Keeping a Guard (Polish Yearbook of International Law, 2016)
Global trade and intercontinental tourism are on the rise in today’s world. This, in turn, leads to more cross-border law suits. Inevitably, jurisdictions will be confronted with legal concepts that are unknown in the host forum. This contribution investigates whether, and to what extent, punitive damages judgments originating in the United States can be enforced against the assets of a defendantin a number of selected Member States of the EU. More specifically, the article explores the possibilities of enforcing American punitive damages judgments in five EU countries, namely Germany, Italy, Spain, France and England. This comparative analysis reveals that the case law in these selected countries is relatively divergent as to the stance adopted towards foreign punitive damages, resulting in different degrees of acceptance of this legal remedy.